Development of a Gamification-Based Mindfulness Information System to Support Emotional Regulation and Reduce Anxiety Levels in Kindergarten Children - Marizki Putri; Yasherly Bachri; Eka Ramadhani Putra (Jurnal Kajian dan Pengembangan Umat, 2026)
The rapid advancement of information technology has created new opportunities to support children's social-emotional learning through interactive digital media. However, information systems that integrate mindfulness practices with gamification remain limited, despite their potential to enhance emotion regulation and reduce anxiety among young children. This study aims to develop a Gamification-Based Mindfulness Information System as an engaging and effective learning medium for kindergarten children. The study employed the Design Science Research (DSR) methodology, consisting of problem identification, system design, development, implementation, and evaluation. A web-based application was developed featuring mindfulness activities, points, badges, achievement levels, and monitoring dashboards for teachers and parents. The software quality was evaluated based on the ISO/IEC 25010 standard, focusing on Functional Suitability, Usability, and Performance Efficiency. System effectiveness was assessed by comparing children's emotion regulation scores before and after the intervention using pre-test and post-test measurements. The results indicate that the developed system achieved excellent software quality and successfully met user requirements. Furthermore, the application significantly improved children's emotion regulation after its implementation. The integration of mindfulness and gamification increased children's engagement in learning, highlighting the potential of the proposed system as an innovative digital tool for supporting social-emotional learning in early childhood education.